Discovery of Pyranoviolin A and Its Biosynthetic Gene Cluster in Aspergillus violaceofuscus - Wei, Xingxing; Chen, Lin; Tang, Jian-Wei; Matsuda, Yudai (Frontiers in Microbiology, 2020)
A new polyketide-non-ribosomal peptide hybrid molecule, pyranoviolin A (1), was discovered from the genome-sequenced fungus Aspergillus violaceofuscus CBS 115571 and was characterized to be the first pyranonigrin analog harboring the C-3 methoxy group. Examination of the genome sequence of the fungus identified a putative biosynthetic gene cluster of 1, which was designated as the pyv cluster. The gene deletion experiment of the polyketide synthase (PKS)-non-ribosomal peptide synthetase (NRPS) hybrid gene in the cluster confirmed the involvement of the pyv cluster in the pyranoviolin A biosynthesis. Finally, a plausible biosynthetic route leading to 1 has been proposed based on the bioinformatic analysis. Our study indicates that metabolite analysis of genome-sequenced microorganisms whose metabolites have been largely unexplored facilitates the discovery of new secondary metabolites along with their biosynthetic gene clusters.